2014
DOI: 10.1144/m40.10
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 10 The rock coast of South and Central America

Abstract: The great variety of climatic conditions, tidal ranges and wave regimes of South and Central America act on a complex geology and tectonic framework. Many of the rock and cliffed coasts of South America are strongly controlled by the occurrence of extensive Cenozoic and Pleistocene sediments that crop out at the coast. Geology and the different uplift rates are a major factor in the whole coastal geomorphology of South and Central America, and consequently are a very important control of the processes and land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 201 publications
(199 reference statements)
0
11
0
Order By: Relevance
“…Short and Woodroffe (2009) estimate 40% of the Australian coast is 'rocky'. Examples of other regional studies with estimates of cliff or rocky coast distribution include: 60% for Japan (Sunamura et al, 2014), 30% for Albania (Simeoni et al, 1997), 29% for Colombia (Blanco-Chao et al, 2014), 37% for South Korea (Choi and Seong, 2014) and 54% for Cuba (Anfuso et al, 2017). Examples of other regional studies with estimates of cliff or rocky coast distribution include: 60% for Japan (Sunamura et al, 2014), 30% for Albania (Simeoni et al, 1997), 29% for Colombia (Blanco-Chao et al, 2014), 37% for South Korea (Choi and Seong, 2014) and 54% for Cuba (Anfuso et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Short and Woodroffe (2009) estimate 40% of the Australian coast is 'rocky'. Examples of other regional studies with estimates of cliff or rocky coast distribution include: 60% for Japan (Sunamura et al, 2014), 30% for Albania (Simeoni et al, 1997), 29% for Colombia (Blanco-Chao et al, 2014), 37% for South Korea (Choi and Seong, 2014) and 54% for Cuba (Anfuso et al, 2017). Examples of other regional studies with estimates of cliff or rocky coast distribution include: 60% for Japan (Sunamura et al, 2014), 30% for Albania (Simeoni et al, 1997), 29% for Colombia (Blanco-Chao et al, 2014), 37% for South Korea (Choi and Seong, 2014) and 54% for Cuba (Anfuso et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lantuit et al (2012) found 35% of the Arctic coast is lithified (however this is not necessarily equivalent to cliffs). Examples of other regional studies with estimates of cliff or rocky coast distribution include: 60% for Japan (Sunamura et al, 2014), 30% for Albania (Simeoni et al, 1997), 29% for Colombia (Blanco-Chao et al, 2014), 37% for South Korea (Choi and Seong, 2014) and 54% for Cuba (Anfuso et al, 2017). In total, the amount of cliffed or rocky coastline has been estimated for 29 independent coastal states, Greenland, Antarctica, and the 48 contiguous United States (Figure 2(a), Supplementary Table I).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher latitudes, on the other hand, tend to have lower rates of chemical erosion but high rates of physical erosion. Ice, in the form of frost as well as sea ice, can dominate rock coast erosion in the polar regions (Chapter 16 by Hansom et al 2014); however these processes do not occur close to the equator in our current climate (Chapters 10 by Blanco-Chao et al 2014 and15 by Woodroffe 2014). The effect of these climatic gradients is expressed most obviously by the landforms created on carbonate lithologies.…”
Section: Climatementioning
confidence: 98%
“…The orientation of the bedding planes, both vertically and horizontally, will have a strong influence on different landforms that emerge as softer materials are eroded preferentially to harder ones, as seen on the rock coasts of the USA and Mexico (Chapter 9 by Hapke et al 2014) as well as South America (Chapter 10 by Blanco-Chao et al 2014). Gulches and sea caves are often formed in this manner through the preferential erosion of weaker units (Trenhaile 1987).…”
Section: Geologymentioning
confidence: 99%